THE EFFECT OF TRAINING AND HUMAN RESOURCE DEVELOPMENT ON WORK DISCIPLINE IN IMPROVING EMPLOYEE PERFORMANCE OF PT INDONESIA ASAHAN ALUMINUM (PERSERO) - Agustriani, Fani (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine how much influence training and human resource development have on work discipline in improving the performance of PT Indonesia Asahan Aluminum (Persero) employees. The sample in this study were 100 employees of PT INALUM (PERSERO). Sampling using purposive sampling, namely the sample taken has been determined by the researcher. The analytical method used is a quantitative descriptive analysis method with multiple linear regression analysis using the path analysis method . Hypothesis testing using the coefficient of determination test (R2), Partial Test (t test), simultaneous test (F test), data processing using SPSS 22. The results of this study indicate that there is no significant effect between training on work discipline in improving the performance of PT INALUM (PERSERO) employees. There is a significant influence between human resource development on work discipline in improving the performance of PT INALUM (PERSERO) employees. The effect of human resource training and development on work discipline in improving the performance of PT INALUM (PERSERO) employees is significant.